2015
DOI: 10.1016/j.renene.2015.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Cost-free feed-in tariffs for renewable energy deployment in Spain

Abstract: Feed-in-tariff (FIT) schemes have been widely employed to promote renewable energy deployment. While FITs may be perceived by consumers as an extra cost, renewable energies cause a noticeable price reduction in wholesale electricity markets. We analyse both effects for the case of the Spanish electricity market during 2010. In particular, we examine the level of FITs that makes savings and extra costs to be similar on an hourly basis. Results are obtained for a wide range of renewable generation scenarios. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 15 publications
0
18
1
2
Order By: Relevance
“…In spite of the fact that the distribution of non-conventional energy resources is significant, policies and the governmental actions framed by the government are significant in bringing updated technologies to public awareness [22][23][24]. As a part of awareness for having access to the governmental policies and their benefits, an approach known as "Footprint" is executed in European countries [25][26][27][28][29]. The integrated energy policy formulated by the government of India has covered all the sources of energy resources, including RE, which helps to develop energy supply options and to increase the exploitation of RE.…”
Section: Global Renewable Energy Scenario: Policy Framework and Currementioning
confidence: 99%
“…In spite of the fact that the distribution of non-conventional energy resources is significant, policies and the governmental actions framed by the government are significant in bringing updated technologies to public awareness [22][23][24]. As a part of awareness for having access to the governmental policies and their benefits, an approach known as "Footprint" is executed in European countries [25][26][27][28][29]. The integrated energy policy formulated by the government of India has covered all the sources of energy resources, including RE, which helps to develop energy supply options and to increase the exploitation of RE.…”
Section: Global Renewable Energy Scenario: Policy Framework and Currementioning
confidence: 99%
“…The support mechanism for PV systems gave the producers the possibility to choose whether to sell the electricity under the FIT tariff or whether to sell the electricity in the free market, taking advantage of a premium above the market price. The FIT policy granted producers for an undefined number of years; a reduction was expected after 25 years [40,41].…”
Section: The Case Of Spainmentioning
confidence: 99%
“…The European Commission adopted in 2007 the so-called EU climate and energy package, which aims to provide 20% of the EU's energy consumption through renewable energy sources by 2020 [1].The need for increasing the share of renewable energies in the total energy production has resulted in a growing interest in marine energiesless developed than other renewables at present but with high potential [2]. Among them, tidal stream energy is one of the most predictable and reliable resources [3].…”
Section: Introductionmentioning
confidence: 99%
“…The tidal stream resource in the Bristol Channel has been the subject of previous assessments 1 , in which areas with a peak flow velocity in excess of 2.5 m s -1 were identified [10]. Predictions about the extraction of this energy suggested that a capacity of 0.6 GW could be installed on the English side of the Outer/Inner Bristol Channel by 2030 [11].…”
Section: Introductionmentioning
confidence: 99%